Natural Hazard Zonation of Bihar (India) Using Geoinformatics A Schematic Approach - Ghosh, Tuhin; Mukhopadhyay, Anirban (SpringerBriefs in Earth Sciences, 2014)
With increased climate variability, aggravated natural hazards in the form of extreme events are affecting the lives and livelihoods of many people. This work serves as a basis for formulating a 'preparedness plan' to ensure the effective policy formulation for planned development. Increased demand and competition with a high degree of variability have forced people to struggle in order to prosper. Good governance and innovative policy formulation are necessary to create a resilient society. This may promote a paradigm shift in the mindset on and perceptions of natural hazards and their impacts on development and growth. This new perspective will make people more concerned about minimizing the loss of life, property, and environmental damage and directly safeguard the development process. This book presents a detailed methodological approach to monitoring meteorological, hydrological, and climate change aspects to help resolve issues related to our environment, resources, and economies in the changing climate situation.